Digital inequality in communication during a time of physical distancing: The case of COVID-19. (July 2021) - Nguyen, Minh Hao; Hargittai, Eszter; Marler, Will
Abstract: In times of physical distancing, such as during the COVID-19 pandemic, people are likely to turn to digital communication to replace in-person interactions. Yet, persisting digital inequality suggests that not everyone will be equally able or disposed to increasing digital communication during a public health crisis. Using survey data from a national sample of U.S. participants ( N  = 2, 925) that we collected during the early months of the pandemic, we analyzed how sociodemographics, living arrangements, and Internet experiences and skills relate to increases and decreases in various digital communication methods. We find that people privileged in their socioeconomic status, their Internet skills and online experiences are more likely to increase and less likely to decrease digital communication during the pandemic. The findings illustrate how digital inequalities can put already disadvantaged groups at greater risk of diminished social contact during a public health crisis. We discuss the theoretical implications of our findings for digital inequality research, the practical implications for inclusive crisis responses, and directions for future research. Highlights: Digital inequality disadvantages some populations in communicating with family and friends during COVID-19. Those with greater socioeconomic and digital privilege more likely increase and less likely decrease digital communication. Disparities in digital communication emerge around sociodemographics, and Internet skills and experiences. Crisis responses should consider those vulnerable to digital exclusion and implement appropriate mitigation strategies.